Use of Electroconvulsive Therapy for Catatonia in Down Syndrome Regression Disorder: A Systematic Review, Case Series, and Analysis - Seri Lim; Kaidi Kang; Elizabeth Oey; Stephanie Santoro; Catherine Franklin; James Luccarelli; Rafael Tamargo; Courtney Hamilton; Sarah Marler; Timothy Adegoke; Jo Ellen Wilson; Joshua Ryan Smith (Journal of Autism and Developmental Disorders, 2026)
Abstract Purpose Down syndrome regression disorder (DSRD) is a condition occurring in young people with Down syndrome. It is associated with functional decline, new onset psychopathology, and increased support needs. DSRD is often associated with catatonia, for which electroconvulsive therapy (ECT) is an effective treatment. However, there are scant studies to guide best practice in this area. Methods We report a case series of 5 patients who have received ECT at Vanderbilt University Medical Center. A systematic review and analysis were conducted, combining this case series with previously reported data in the literature. Results This analysis included data from 27 patients, 5 from the VUMC case series and a further 22 from 14 studies. Combining all patients from case series and the systematic review, there were 17 pre-ECT and 15 post-ECT Bush Francis Catatonia Rating Scale (BFCRS) scores reported from 7 sites/studies. The mean pre-ECT BFCRS score from all patients was 17.40 (SD = 5.72) and the mean post-ECT BFCRS score was 4.40 (SD = 5.26). A generalized estimating equations analysis revealed that there was a significant difference in the expected BFCRS score before and after receiving ECT treatment ( β = -13.00 with 95%, p < 0.001), suggesting that the ECT treatment had a significant effect on reducing the BFCRS scores. No severe adverse events were reported. Conclusion ECT is associated with clinical improvement in patients with catatonia in the context of DSRD in this systematic review and analysis. More research is needed to provide a more robust evidence base.